Modeling of Three-Phase Induction Motor Performance under Faulty Inverter Condition Using MATLAB GUI and Simulink - Rasyadan, Amir; Yaacob, Sazali (International Journal of Engineering and Technology, 2018)
Recent advancement in semiconductor technologies have extended the use of induction motors in a wide area of variable speed applications. Traditional fixed speed drives are becoming obsolete and majority of the applications now require inverter-based drives for a more efficient and precise speed control. Nonetheless, the use of power electronic devices came with an increased possibility of the motor drive system failures mainly caused by the switching device itself. Hence, in the development of an induction motor drive system, it is crucial to study not only on the induction motor but also taking into considerations of the inverter system under healthy and faulty conditions. Computer simulation models are often used to get an insight of the system behaviour; however, the implementation of such model is a fairly complicated task and most of the previous literatures does not emphasize on the implementation of the model. This paper is intended to present a computer simulation model using MATLAB Simulink to simulate the power switches open-circuit and short-circuit faults that may occur in an inverter fed induction motor drive. The sub models of the system include an induction motor direct-quadrature (dq) model, a voltage source inverter (VSI) driven by an open-loop sinusoidal pulse width modulation (SPWM) and a simple graphical user interface (GUI) to allow user control on the input parameters during simulation run. The dynamic behaviour of the motor speed, phase current and electromagnetic torque during healthy and faulty condition can be simulated. The simulation shows that the inverter fails in shaping proper outputs under open switch resulting in degraded motor performance while shorted switch lead to abnormal overcurrent forcing the motor to stop.Â Â